On a product-type operator between Hardy and α-Bloch spaces of the upper half-plane - Stevo Stević; Ajay K. Sharma (Journal of Inequalities and Applications, 2018)
Abstract Recently we have introduced a product-type operator and studied it on some spaces of analytic functions on the unit disc. Here we start investigating the operator on the space of analytic functions on the upper half-plane. We characterize the boundedness and compactness of the operator between Hardy and α-Bloch spaces on the domain.